2022
DOI: 10.1155/2022/3833489
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib and Ginsenoside-Rb1 Synergetically Control the Growth of Hypopharyngeal Carcinoma Cells

Abstract: Background. Apatinib is an anticancer drug known to inhibit the vascular endothelial growth factor receptor-2 (VEGFR-2) through regulating tyrosine kinases. Drug resistance and reduced activity in various cancers is the matter of great concern; thus, researchers opt to use combination of the two or more drugs. So far, its gynergetic anticancer role with a traditional Chinese drug Ginsenoside-Rb1 (G-Rb1) has not been studied in cancers including hypopharyngeal carcinoma. Objective. The current study is aimed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…GRb1 increased the intracellular drug concentration of cisplatin by targeting ABCB1 and the Hedgehog pathway, reversing cisplatin resistance in A549/DDP cells and improving its efficacy (15). In nasopharyngeal carcinoma cells, Li et al reported that GRb1 combined with apatinib could inhibit tumor cell glycolysis, reduce tumor cell proliferation and migration, upregulate the immune-related indices CD3 + and CD4 + , increase apoptosis, enhance the expression of immune regulatory molecules, and exert synergistic anticancer effects on nasopharyngeal carcinoma cells via ginsenosides to inhibit the malignant progression of nasopharyngeal carcinoma (16). In cervical cancer chemotherapy, paclitaxel (PTX) resistance has become a major challenge and therapeutic difficulty.…”
Section: Chinese Herb Monomer 21 Ginsenosidesmentioning
confidence: 99%
“…GRb1 increased the intracellular drug concentration of cisplatin by targeting ABCB1 and the Hedgehog pathway, reversing cisplatin resistance in A549/DDP cells and improving its efficacy (15). In nasopharyngeal carcinoma cells, Li et al reported that GRb1 combined with apatinib could inhibit tumor cell glycolysis, reduce tumor cell proliferation and migration, upregulate the immune-related indices CD3 + and CD4 + , increase apoptosis, enhance the expression of immune regulatory molecules, and exert synergistic anticancer effects on nasopharyngeal carcinoma cells via ginsenosides to inhibit the malignant progression of nasopharyngeal carcinoma (16). In cervical cancer chemotherapy, paclitaxel (PTX) resistance has become a major challenge and therapeutic difficulty.…”
Section: Chinese Herb Monomer 21 Ginsenosidesmentioning
confidence: 99%
“…Ginsenoside Rb1 combined with apatinib can significantly increase the levels of CD3 + and CD4 + cells and the proportion of CD4 + to CD8 + cells It has stronger immunomodulatory activity than single-use treatment. [37] Rb1 alone can improve proliferation, inflammation, and adipogenesis induced by TNF-α treatment of adipocytes, and when combined with berberine (BBR), which has the same efficacy, it has a synergistic protective effect on TNF-α-induced inflammation in adipocytes by inhibiting the NF-кB signaling pathway. [38] Ginsenosides and polysaccharides can regulate the expression of T cell receptors (TCR) and mediate the activation of T lymphocytes.…”
Section: Increased T Cell Activitymentioning
confidence: 99%
“…Active substances in black ginseng can improve the activity of T cells and enhance the immune response through synergistic effects with other drugs. Ginsenoside Rb1 combined with apatinib can significantly increase the levels of CD3 + and CD4 + cells and the proportion of CD4+ to CD8+ cells It has stronger immunomodulatory activity than single‐use treatment [37] . Rb1 alone can improve proliferation, inflammation, and adipogenesis induced by TNF‐α treatment of adipocytes, and when combined with berberine (BBR), which has the same efficacy, it has a synergistic protective effect on TNF‐α‐induced inflammation in adipocytes by inhibiting the NF‐κB signaling pathway [38] …”
Section: The Active Ingredient In Black Ginseng and Anti‐inflammatory...mentioning
confidence: 99%
“…Recently, studies have confirmed that ginsenosides can be used in combination with a variety of drugs to enhance the inhibitory effect on cancer cells or increase the sensitivity to traditional chemotherapy drugs ( Choi et al, 2013 ). For example, ginsenoside Rb1 and apatinib work synergistically to enhance the inhibition of growth of pharyngeal cancer cells ( Li Y. et al, 2022 ). Combination therapy of ginsenoside Rg3 and chemotherapeutics drugs against BC has been demonstrated.…”
Section: Future Prospectsmentioning
confidence: 99%